Effect of hybrid drying technique on non-traditional Chicory (Cichorium intybus L.) herb: Phytochemical, antioxidant characteristics, and optimization of process conditions - Zahoor, Insha; Anjum, Nadira; Ganaie, Tariq Ahmad; Allai, Farhana Mehraj; Al-Ghamdi, Abdullah Ahmed; Abbasi, Arshad Mehmood; Wani, Sajad Ahmad (Frontiers in Sustainable Food Systems, 2022)
This research investigated the influence of microwave assisted fluidized bed drying (MAFBD) on the antioxidant and phytochemical characteristics of Chicory. Microwave power, temperature and air velocity were used as process variables varied between 180-540 W, 50-70°C and 15-20m/s, respectively. The responses determined for deciding the optimal criteria were total phenolics content, ascorbic acid, DPPH radical scavenging activity, total chlorophyll, carotene content, total flavonoid content, tannin and saponin content of the dried chicory. Statistical analyses were done by using Response surface methodology, which showed that independent variables affected the responses to a varied extent. Design expert predicted 462.30 W microwave power, 70 °C temperature, and 15m/s air velocity as optimum conditions to obtain highest desirability for the dried chicory. At optimum conditions, validation experiment was done to ensure the suitability of models. Taking the aforesaid results into consideration, our study recommended MAFBD as a promising technique with minimum changes in antioxidant and phytochemical content of chicory.